PENGARUH WORK FAMILY CONFLICT DAN AMBIGUITAS PERAN TERHADAP INTENTION TO QUIT DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING (Studi pada HOTEL GRAND EDGE SEMARANG) - Munda, Agres Oktavia; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2018)
The objectives of this research are to define and comprehensively analyze the influence of work family conflict and role ambiguity towards intention to quit by conducting work stress as the intervening variable. This research was conducted by passing the questionaires to 50 staffs in Grand Edge Hotel, Semarang.It applied multiple regression as method analysing the data. In testng the data, validity test, reliability test, classical assumption test, and determinant coefficient test, F test, T test, and Test of Sobel were conducted in order to check the mediation effectAs the result, it showed that work family conflict was positively and significanly influenced work stress and intention to quite, role ambiguity was positively and significanly influenced work stress and intention to quite. Work stress was to mediate relation between work family conflict and role ambiguity towards intention to quit.